THE CHALLENGES AND PROSPECTS OF NIGERIA COPYRIGHT ADMINISTRATION IN A DIGITAL ARTIFICIAL INTELLIGENCE AGE - Ibe, Ikenna U.; Udeoji, Noel N. (ABUAD Private and Business Law Journal, 2019)
Copyright is one of the several existent intellectual property rights which seek to protect original works of authorship fixed in any medium of expression known or later to be developed. While this form of protection exists, the influx of digital revolution also persists to cause a strain in copyright administration and protection due to evolution in means of replication, manipulation, reproduction, dissemination, access to copyrighted materials, etc. This work aimed at examining the approach of the Nigerian copyright system and her administrative structure in the face of digital and internet evolution, by extension Artificial Intelligence (AI) revolution which is an emerging technology. Is the new copyright system staller enough to meet the increasing requirements of protection for copyrighted materials, or capable to simultaneously evolve with digital and internet revolution? This work further seeks to examine the inherent weakness in the present copyright system despite the new enactment. The doctrinal methodology was employed in this work. It was discovered that despite the introduction of Copyright Act of 2022, which incorporates several multilateral agreements, expands copyright protection to online works, made provisions regarding technological protection, a practical overhaul of the entire gamut of the copyright system to reflect the intendment of this Act is strictly recommended. Conclusively, incorporation of technology and adequate manpower in the copyright administration will meet the technological requirements of providing protection against digital and online infringement which AI is now a critical tool.